Radioprogramma ORT: interview met E. Etty, B. en E. Santen n.a.v. het overlijden van Sal Santen, 2 augustus 1998 (1998)
Radioprogramma ORT: interview met E. Etty, B. en E. Santen n.a.v. het overlijden van Sal Santen, 2 augustus 1998.